Pengembangan LKPD Bermuatan Assemblr Edu Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa SMP Kelas VIII Pada Materi Kubus dan Balok - Laurensia Sonia; Jamilah; Muchtadi (LPD Universitas PGRI Pontianak, 2026)
This study aimed to develop a Student Worksheet (LKPD) integrated with Assemblr EDU to improve the mathematical problem-solving ability of Grade VIII junior high school students on cube and rectangular prism material. The research used a Research and Development (R&D) approach with the ADDIE model, involving 22 students of class VIII A at SMP Negeri 13 Pontianak. The results showed that the LKPD met the criteria of very valid (88.74%), very practical (91.65%), with a significant improvement in problem-solving ability (pretest 17 → posttest 83, Wilcoxon Test Sig. = 0.000), and effective with an average N-Gain of 0.77 in the high category. Therefore, the Assemblr EDU-integrated LKPD is suitable for use as a mathematics learning medium in junior high school. Keywords: Student Worksheet, Assemblr EDU, Problem-Solving Ability, Cube and Rectangular Prism.